Using basic physics to avoid injuries - Morrow, C. (The Professional Skater PS Magazine, 2015)
The human body that jumps with maximum distance and height first, isolating the double, triple, or quadruple rotational force to the air-borne apex segment of the jump will be able to stop that rotation by spotting the landing line, in effect, stopping the head turning in the direction of rotation, opening the arms, and unhinging the crossed leg to hold beside the other in preparation to push out the landing, facilitated by the straighter, much less vertical touch-down and clean back outside edge. Further, the human body that employs all of the above in jumping, having prepared for a straighter edged, diffused stress landing, can lift away and pull back on the torso as it gently flexes then expands both legs at the touchdown. The skater who applies all of the above techniques originated by Mr. Lussi for jumping will measurably reduce falling and avoid leg and back stress fractures and many other stress and jumping-related injuries. Misha Petkevich: "It's a very simple reason why his skaters were so consistent... understanding the rotational forces that are created in skating and learning how to control those."